The Financial Performance of Ternate City’s Government: Analysis Before and During The Pandemic Covid-19 - Abdullah, Sehat; Zam-Zam, Irfan; Suwito, Suwito (Economics, Business, Accounting & Society Review, 2022)
This study aims to analyze the Financial Performance of the Ternate City Government in the period before and during the Covid-19 pandemic. The method used in this research is a comparative descriptive method with a quantitative approach. The results of the study show that 1) The level of regional financial independence ratio does not change the level of regional financial independence before and during the Covid-19 Pandemic; 2) The level of PAD effectiveness ratio does not change the effectiveness ratio of Ternate City's original income for the period before and during the Pandemic. Covid-19; 3) The level of regional expenditure efficiency ratio there is no change in the level of regional financial efficiency of Ternate City before and during the Covid-19 Pandemic; 4) The level of regional financial growth ratio there is a decrease in regional financial growth during the covid-19 pandemic; 5 There is no change in the level of compatibility of spending in the Ternate City area before and during the Covid-19 Pandemic.